2006
DOI: 10.1080/17439760500373174
|View full text |Cite
|
Sign up to set email alerts
|

The role of positive psychology constructs in predicting life satisfaction in adolescents with and without cognitive disabilities: An exploratory study

Abstract: Positive psychology has begun to foster change in the study of adolescence by directing increased attention to the importance of building on adolescents' strengths and abilities as a means to promote positive outcomes. The purpose of this study was to explore the associations between hope, optimism, locus of control, self-determination, and life satisfaction in adolescents with and without cognitive disabilities using structural equation modeling. The results demonstrated comparability in the measurement of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 66 publications
7
74
1
8
Order By: Relevance
“…gender) or experience with selfdetermination and family support for self-determination within or across cultures. Given previous research (Nota et al, 2007;Shogren et al, 2006) that has suggested these variables may influence student self-determination, further research is needed to explore the influence of these characteristics across cultures. Second, our sample was limited to Italian and American adolescents, future research including a more diverse sample of nationalities is needed.…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…gender) or experience with selfdetermination and family support for self-determination within or across cultures. Given previous research (Nota et al, 2007;Shogren et al, 2006) that has suggested these variables may influence student self-determination, further research is needed to explore the influence of these characteristics across cultures. Second, our sample was limited to Italian and American adolescents, future research including a more diverse sample of nationalities is needed.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Increasingly, the application of this theory to adolescents without disabilities has been explored (Shogren, Lopez, Wehmeyer, Little, & Pressgrove, 2006;. Researchers argue that the f SDT has relevance for improving the outcomes of all students as they transition to adulthood, not just adolescents with disabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted on samples of adolescents with ID revealed that positive individual characteristics (e.g. optimism, self-efficacy) were a good predictor of higher quality of life (Biggs & Carter, 2016) and life satisfaction (Shogren et al, 2006).…”
Section: Intellectual Abilities and Resiliencymentioning
confidence: 99%
“…Optimism in a learning context is associated with learner autonomy and self-determination in relation to the accomplishment of learning tasks and goals (Shogren, Lopez, Wehmeyer, Little, & Pressgrove, 2006). The optimistic learner believes in the possibility of positive outcomes and that these can be attained through personal effort or persistence (Bryant & Cvengros, 2004).…”
Section: Optimismmentioning
confidence: 99%